(untitled) (Bangladesh Journal of Agricultural Research, 2016)
Laboratory studies on soil fertility evaluation was carried out across major agroecological zones (AEZs) of Bangladesh to know the nutrient status of soils and to relate those with soil properties like pH, organic matter, CEC, and clay content. Thirty five composite soil samples were collected from intensive crop growing sites, which covered 17 AEZs of Bangladesh. After proper processing, the samples were analyzed for texture, pH, organic carbon, CEC, exchangeable cations (K, Ca, Mg and Na), total N, available P and S following standard methods. The textural class of the soils collected from AEZ 12 and 13 appeared to be mostly clay. Clay loam soil was found in AEZ 4, 8, 9, 11, 25 and 28. Loamy soil was seen in AEZ 1 while AEZ 22, 23 and 29 were mostly sandy textured. The results revealed that 65.7% of the tested soil was acidic while 25.7% was alkaline in nature. All the tested soils showed lower pHKCl compared to pHH2O thus possessed negative charge. About 68.6% of the collected soils contained low (1.10-1.70%) level of organic matter, 25.7% soils retained it at medium level (1.71-2.40) and 5.7% soils at very low level (<1.0%). All the tested soils appeared to be deficient (< 0.12%) in nitrogen content. 68.6% soil samples had the low level of available P while only 8.6% retained it an optimum amount. About 80% of the tested soils contained low level of available S (7.9- 14.7 mg kg -1) although coastal regions soils hold higher amount of available S. High CEC (20-38 cmol kg-1) was found in clay rich soils of AEZ 10, 11, 12, and 13. Study revealed that 40% of the collected soils were very low, 31.4% were low, 8.6% each of medium and optimum, and 11.4% contained high level of exchangeable K. The calcareous soils (AEZ 10, 11, 12 and 13) contained very high level of Ca. Non calcareous soils also showed fairly good level of Ca content except AEZ 1, 3, 23 and 29. Sandy textured soils of greater Dinajpur, Rangpur, Moulvibazar showed lower level of exchangeable Mg. About 86% of the tested soils had the lower (< 2%) potassium saturation percentage (KSP), which needs K application for sustainable crop production. Estimate showed that 44% variability for CEC may be attributed by clay content and the relationship was significant (p = 0.05). Again, 50.4 and 65.6% variability in exchangeable K and Mg, respectively may be governed by clay content of the soils, while such relationship for Ca was non-significant. CEC may contribute 62.2, 92.3 and 83.9% variability for exchangeable K, Ca and Mg content in soils, respectively. The fertility status of most of the studied soils (except AEZ 10, 12, 13 and to some extent 11) appeared to be low to very low, which demand judicious management in order to achieve food security and to conserve the soil fertility. Bangladesh J. Agril. Res. 41(4): 735-757, December 2016